Agent-Based Models: Tools - (:unkn) unknown (Springer Link, 2020)
The methodological focus of this book is the object- and agent-based simulation. No state equations or system dynamics schemes are used. Recall that in the discrete object-based modeling, we create objects that behave according to the user-defined rules and execute their events in discrete moments of the model time. The agent-based models manage objects called agents, which are equipped with certain “intelligence.” They can take decisions, optimize their actions, and interact with each other and with the environment. Agent-based models (ABMs) are a type of microscale models that simulate the simultaneous operations and interactions of multiple agents in an attempt to recreate and predict the appearance of global complex phenomena.